Frequency of Newly Diagnosis Patients of T2DM and COPD in the Department of Pulmonology at HMC Hospital Peshawar a Qualitative, Cross-Sectional, and Observational Study - Muhammad Asif Khan, Anwar Ul Haq, Imran Qadir Khattak, Farhan Zeb, Hameed Ullah, Muhammad Awais (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Since the immune system weakens in people with DM, Tuberculosis is one of the most prevalent infectious diseases . Objective: This study aimed to determine the prevalence of various forms of active Tuberculosis among people with diabetes. Methodology: This Cross-sectional, observational, and qualitative methods were use din this investigation. Patients with diabetes whom et the inclusion criteria (cough with or without expectoration, hemoptysis, persistent fever, and unexplained weight loss) were questioned in one of three pulmonology department outpatient clinics (OPDs). The short duration of diabetes, ageless than ten and more than 85 years, and all cases of immune compensation and secondary diabetes were excluded. When looking in to the possibility of TB, a thorough history, clinical exam, and tests were performed once permission was obtained. All of the information was loaded into SPSS version 24 for further analysis As a result, 151 people were chosen for further testing for TB out of a total of 550 patients questioned. Active TB was found in just 19 individuals (13percent).The mean age was5 2.03±10.01,the male-to-female ratio was01.08:01.04,and the mean duration of diabetes observed was 10.04years. All were type 2 diabetics exception which turned out to be type 01. Out of the total cases of Tuberculosis, 54% were determined to be pulmonary cases and45% were extrapulmonary cases. Pulmonary cancer had an 11% primary rate, an 18% secondary rate, and a 6% milliary rate. Smear positivity was identified in 57% of patients, and multidrug-resistant Tuberculosis was discovered in 21%, about twice the rate seen in non-diabetic cases. Results: As a result, 151 people were chosen for further testing for TB, and 550 patients were questioned. Active TB was found in just 19 individuals (13 per cent). The mean age was 52.03 ±10.01, the male-to-femaleratiowas01.08:01.04,and the mean duration of diabetes observed was 10.04 years. All were type 2 diabetics except one which turned out to be type 01. Out of the total cases of Tuberculosis, 54% were determined to be pulmonary cases and 45% were extra pulmonary cases. Pulmonary cancer had an11%primary rate,and 18% secondary rate, and a 6%milliaryrate.Smear positivity was identified in 57% of patients, and multidrug-resistant Tuberculosis was discovered in 21%,about twice the rate seen in non diabetic cases. Conclusion: Tuberculosis frequency is more prevalent in people with diabetes than in the general population. Extrapulmonary Tuberculosis occurs more often in people with diabetes compared to those without the disease. Diabetics should be screened more often for the illness so that MDR-TB doesn’t spread and become a major public health issue in this underdeveloped nation. Keywords: Diabetes, pulmonary Tuberculosis, extra-pulmonary Tuberculosis, tuberculosis variants, drug-resistant Tuberculosis